Stopping Decisions: Information Order Effects on Nonfocal Evaluations. (August 2013) - Yu, Michael; Gonzalez, Cleotilde
Objective: We investigated how the order in which information is presented affects when a person decides to stop performing a task. Background: A stopping decision is a decision to stop performing a task on the basis of a sequence of cues. Previous order-effects models do not account for how these contexts limit available working memory for making such decisions. Method: Participants decided how long to perform a task known as the Work Hazard Game that began by rewarding points but later cost points if work continued after an unannounced "emergency." An additive sequence of cues indicated the probability of an emergency. Study 1 involved a three-group design with cue sequences that indicated the same risk at each decision point but whose final cue presented a high, medium, or low probability. Study 2 had a 2 × 2 design with high or low final cues and an easy or a challenging task. Results: In Study 1, participants stopped sooner when the most recent cue presented a high rather than low probability ( p = .09), despite the same emergency risk. In Study 2, participants stopped sooner when the most recent cue presented a high rather than low probability for the challenging task but not for the easy task ( p = .08). Conclusion: Stopping decisions appear sensitive to the most recent cue observed while experiencing task load. Participants responded to the same risks differently only on the basis of a change in presentation. Application: Findings may be relevant for research and training for hazardous jobs, such as subsurface coal mining, fishing, and trucking.